Trust and the Health of Organizations - Bruhn, John G. author. aut Link
XIII, 222 p.
Keywords: Leaders are usually held responsible for the trust, health and success of an organization, but it is the culture of organizations that provides the true foundation for these important factors. The leader's personality and skills influence how a trustful environment and working relationship is created, but the organization has a culture, tradition and experience of its own which influences the leader's success. The level of trust in an organization's culture will ultimately determine whether or not it is trustful, healthy and successful. Based on the interview of current and former chief executive officers from profit and non profit organizations to record their experiences in creating trust in their environment and their perceptions of the health of their organizations. The collected data reveals: - The qualities of a "trusted" leader; - How they created trust or; - How trust was destroyed in organizations; - How leaders worked in distrustful environments; - How to create a more healthy organization. This timely work will be of interest to organizations and occupational sociologists, human resource workers, social psychologists, and students of management courses.